Fermi Arcs Dominating the Electronic Surface Properties of Trigonal PtBi2 - Sven Hoffmann; Sebastian Schimmel; Riccardo Vocaturo; Joaquin Puig; Grigory Shipunov; Oleg Janson; Saicharan Aswartham; Danny Baumann; Bernd Büchner; Jeroen van den Brink; Yanina Fasano; Jorge I. Facio; et al. (Advanced Physics Research)
Abstract Materials combining topologically non‐trivial behavior and superconductivity offer a potential route for quantum computation. However, the set of available materials intrinsically realizing these properties are scarce. Recently, surface superconductivity has been reported in PtBi2 in its trigonal phase and an inherent Weyl semimetal phase has been predicted. Here, based on scanning tunneling microscopy experiments, the signature of topological Fermi arcs are revealed in the normal state patterns of the quasiparticle interference. It is shown that the scattering between Fermi arcs dominates the interference spectra, providing conclusive evidence for the relevance of Weyl fermiology for the surface electronic properties of trigonal PtBi2.